2008
DOI: 10.1038/bjp.2008.327
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic state, high plasma insulin and angiotensin II combine to augment endothelin‐1‐induced vasoconstriction via ETA receptors and ERK

Abstract: Background and purpose: Mechanisms associated with the enhanced contractile response to endothelin-1 in hyperinsulinaemic diabetes have been examined using the rat aorta. Functions for angiotensin II, endothelin-1 receptor expression and extracellular signal-regulated kinase (ERK) have been investigated. Experimental approach: Streptozotocin-induced diabetic rats were infused with angiotensin II or, following insulin treatment, were treated with losartan, an angiotensin II receptor antagonist. Contractions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…We (32,33) and others (34) have previously reported that the above losartan dosage regimen has beneficial effects on vascular functions in a number of disease models in rats. Moreover, in a very recent study, again using the above losartan dosage regimen, we noted that Ang II-mediated contraction was largely suppressed in mesenteric arteries obtained from losartan-treated GK or Wistar rats (35).…”
Section: Animals and Experimental Designmentioning
confidence: 90%
“…We (32,33) and others (34) have previously reported that the above losartan dosage regimen has beneficial effects on vascular functions in a number of disease models in rats. Moreover, in a very recent study, again using the above losartan dosage regimen, we noted that Ang II-mediated contraction was largely suppressed in mesenteric arteries obtained from losartan-treated GK or Wistar rats (35).…”
Section: Animals and Experimental Designmentioning
confidence: 90%
“…Experimental type 1 diabetic rats were induced with a single intravenous injection of STZ (65 mg/kg dissolved in citrate buffer), as described previously. [22][23][24] As a control, age-matched rats were injected with citrate buffer alone. All animals were given a standard laboratory diet and water ad libitum until the rats were 31 or 32 weeks old (viz.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this well-described stimulation of NO synthesis by insulin, insulin also stimulates synthesis of the vasoconstrictor, endothelin-1 (ET-1), which can dominate under certain circumstances [20]. The molecular mechanisms by which insulin stimulates NO and ET-1 synthesis are discussed further below.…”
Section: The Effect Of Insulin On the Endotheliummentioning
confidence: 99%